Effect of nonadiabatic electronic-vibrational interactions on the transport properties of single-molecule junctions - Erpenbeck, André; Haertle, R.; Thoss, Michael (Physical Review B, 2015)
The interaction between electronic and vibrational degrees of freedom in single-molecule junctions may result from the dependence of the electronic energies or the electronic states of the molecular bridge on the nuclear displacement. The latter mechanism leads to a direct coupling between different electronic states and is referred to as nonadiabatic electronic-vibrational coupling. Employing a perturbative nonequilibrium Green’s function approach, we study the influence of nonadiabatic electronic-vibrational coupling in model molecular junctions. Thereby, we distinguish between systems with well-separated and quasidegenerate electronic levels. The results show that the nonadiabatic electronic-vibrational interaction can have a significant influence on the transport properties. The underlying mechanisms, in particular the difference between nonadiabatic and adiabatic electronic-vibrational couplings, are analyzed in some detail.

Hierarchical quantum master equation approach to charge transport in molecular junctions with time-dependent molecule-lead coupling strengths - Erpenbeck, André; Götzendörfer, Lukas; Schinabeck, Christian; Thoss, Michael (European Physical Journal - Special Topics, 2019)
Time-dependent currents in molecular junctions can be caused by structural fluctuations or interaction with external fields. In this paper, we demonstrate how the hierarchical quantum master equation approach can be used to study time-dependent transport in a molecular junction. This reduced density matrix methodology provides a numerically exact solution to the transport problem including time-dependent energy levels, molecule-lead coupling strengths and transitions between electronic states of the molecular bridge. Based on a representative model, the influence of a time-dependent molecule-lead coupling on the electronic current is analyzed in some detail.
CRIS-Team WoS Importer:2019-04-12

Hierarchical quantum master equation approach to electronic-vibrational coupling in nonequilibrium transport through nanosystems - Schinabeck, Christian; Erpenbeck, André; Haertle, R.; Thoss, Michael (Physical Review B, 2016)
Within the hierarchical quantum master equation (HQME) framework, an approach is presented, which allows a numerically exact description of nonequilibrium charge transport in nanosystems with strong electronic-vibrational coupling. The method is applied to a generic model of vibrationally coupled transport considering a broad spectrum of parameters ranging from the nonadiabatic to the adiabatic regime and including both resonant and off-resonant transport. We show that nonequilibrium effects are important in all these regimes. In particular, in the off-resonant transport regime, the inelastic cotunneling signal is analyzed for a vibrational mode in full nonequilibrium, revealing a complex interplay of different transport processes and deviations from the commonly used G0/2 rule of thumb. In addition, the HQME approach is used to benchmark approximate master equation and nonequilibrium Green's function methods.
EAM Import::2019-03-13

Thermoelectricity of near-resonant tunnel junctions and their relation to Carnot efficiency - Popp, Matthias Albert; Erpenbeck, André; Weber, Heiko B. (Scientific Reports, 2021)

Vibrationally dependent electron-electron interactions in resonant electron transport through single-molecule junctions - Erpenbeck, André; Haertle, R.; Bockstedte, Michel Georg; Thoss, Michael (Physical Review B, 2016)
We investigate the role of electronic-vibrational coupling in resonant electron transport through single-molecule junctions, taking into account that the corresponding coupling strengths may depend on the charge and excitation state of the molecular bridge. Within an effective-model Hamiltonian approach for a molecule with multiple electronic states, this requires to extend the commonly used model and include vibrationally dependent electron-electron interaction. We use Born-Markov master equation methods and consider selected models to exemplify the effect of the additional interaction on the transport characteristics of a single-molecule junction. In particular, we show that it has a significant influence on local cooling and heating mechanisms, it may result in negative differential resistance, and it may cause pronounced asymmetries in the conductance map of a single-molecule junction.
UnivIS-Import:2017-12-18:Pub.2016.nat.dphy.ITP.ppem.vibrat